Effect Of Membrane Selectivity And Configuration On Purity And Recovery Of Hydrogen From Syngas - Thamudoran, Mohashiniee (Universiti Sains Malaysia, 2021)
In this thesis, simulation of a membrane gas separation system for purification of hydrogen from syngas has been discussed. The simulation was done to study the effects of membrane selectivity, flow configuration, stage cut and feed pressure on the purity and recovery of hydrogen from syngas. In order to model the membrane, a complete mixing model was applied to study these effects. The mathematical modelling involved in the simulation was done in Mathcad and the results were analysed using the analysis of variance (ANOVA) under the Response Surface Methodology (RSM) method. In order to produce high purity hydrogen that is accepted as commercial industrial grade hydrogen, we studied two types of flow configuration models. Configuration 1 involves a carbon dioxide permeable membrane while configuration 2 model involves a hydrogen permeable membrane. As a result, it is noticed that in the first configuration, at the stage cut of 0.2, feed pressure of 5 bar and CO2/H2 selectivity of 1500, the highest purity of hydrogen at 52.24% and recovery of 59.58% at the permeate stream is achieved. Meanwhile in the retentate stream, the purity and recovery of carbon dioxide achieved is 52.21% and 55.53% respectively. The second configuration is when a hydrogen permeable membrane is applied. This configuration results in the highest possible purity of hydrogen of 100% with recovery of 32.52% and carbon dioxide purity and recovery at 27.35% and 90.42% respectively, at stage cut of 0.2, feed pressure of 25 bar and H2/CO2 selectivity of 500.